2014
DOI: 10.1038/bcj.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

The role of front-line anthracycline-containing chemotherapy regimens in peripheral T-cell lymphomas

Abstract: Peripheral T-cell lymphomas (PTCLs) are a heterogenous group of aggressive non-Hodgkin's lymphomas that are incurable in the majority of patients with current therapies. Outcomes associated with anthracycline-based therapies are suboptimal, but remain the standard of care for most patients, even though the benefits of this approach remain uncertain. This study retrospectively examined outcomes in a cohort of North American PTCL patients treated with both anthracycline- and nonanthracycline-containing regimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…Moreover, anthracycline-treated patients were more prone to receive bone marrow transplantation, either in first or second remission. 39 More intensive chemotherapy regimens have not proven to be more effective than CHOP in historical controls 38 ; moreover, in a phase 3 randomized study by Simon et al, an alternative induction schedule including etoposide, ifosfamide, and cisplatin, alternating with doxorubicin, bleomycin, vinblastine, and dacarbazine did not show any superiority in terms of event-free survival (EFS) over CHOP (given every 21 days), thus confirming CHOP as the reference regimen for PTCL patients. 40 The role of adding etoposide to CHOP (CHOEP) during induction was investigated in depth by the German High-Grade Non-Hodgkin Lymphoma Study Group 41 : CHOEP, given either every 14 or 21 days, improved response and EFS rates in young patients with normal LDH levels (3-year EFS was 70.5% after CHOEP and 51.0% after CHOP, P 5 .004), although 3-year OS did not significantly differ between the 2 groups (81.3% for CHOEP vs 75.2% for CHOP, P 5 .285).…”
Section: First-line Treatmentmentioning
confidence: 99%
“…Moreover, anthracycline-treated patients were more prone to receive bone marrow transplantation, either in first or second remission. 39 More intensive chemotherapy regimens have not proven to be more effective than CHOP in historical controls 38 ; moreover, in a phase 3 randomized study by Simon et al, an alternative induction schedule including etoposide, ifosfamide, and cisplatin, alternating with doxorubicin, bleomycin, vinblastine, and dacarbazine did not show any superiority in terms of event-free survival (EFS) over CHOP (given every 21 days), thus confirming CHOP as the reference regimen for PTCL patients. 40 The role of adding etoposide to CHOP (CHOEP) during induction was investigated in depth by the German High-Grade Non-Hodgkin Lymphoma Study Group 41 : CHOEP, given either every 14 or 21 days, improved response and EFS rates in young patients with normal LDH levels (3-year EFS was 70.5% after CHOEP and 51.0% after CHOP, P 5 .004), although 3-year OS did not significantly differ between the 2 groups (81.3% for CHOEP vs 75.2% for CHOP, P 5 .285).…”
Section: First-line Treatmentmentioning
confidence: 99%
“…TCL are currently classified by WHO criteria [2,3], with the most common subtypes being peripheral TCL-not otherwise specified (PTCL-NOS), angioimmunoblastic TCL (AITL), anaplastic large cell (ALCL), and the predominant subsets of cutaneous TCL (CTCL), Sézary syndrome (SS) and mycosis fungoides (MF). The long-term outcome of the non-CTCL groups remains poor with ∼30% of patients being cured [4]. Induction therapy is typically with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or CHOP plus etoposide (CHOPE), and eligible patients typically receive autologous stem cell transplant in the first remission [5].…”
mentioning
confidence: 99%
“…9,30 Despite the recent approval of the histone deacetylase inhibitors romidepsin and belinostat and the antifolate pralatrexate, additional new agents are needed to improve outcome for these patients. In this report, we present promising results with the single-agent mTORC1 inhibitor everolimus for relapsed TCL.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advances, the overall prognosis of TCL remains inferior to B-cell NHL with only 30% of patients cured with frontline therapy. 9 The PI3K/Akt/mammalian target of rapamycin (mTOR) pathway has become an important focus for cancer therapeutic interventions with the approval of the PI3Kd inhibitor idelalisib for chronic lymphocytic leukemia and indolent B-cell NHL, 10,11 and the mTORC1 inhibitors temsirolimus and everolimus for solid tumors. We have reported that the PI3K/mTOR pathway is activated in NHL cells 12 and that mTORC1 inhibitors have activity in relapsed B-cell NHL.…”
Section: Introductionmentioning
confidence: 99%